Evaluation of Referral System Readiness in Handling Cardiovascular Emergencies in Hospitals - Kurniawan, Rudi Erwin (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Cardiovascular emergencies are among the leading causes of morbidity and mortality worldwide. An effective referral system is crucial to ensuring patients receive timely and optimal care. This study aims to evaluate the readiness of the referral system in handling cardiovascular emergencies in hospitals using a literature review and descriptive analysis method. The findings indicate that infrastructure readiness, medical personnel capacity, and coordination between healthcare facilities play crucial roles in the effectiveness of the referral system. However, challenges such as limited medical transportation facilities and lack of integration of information technology in referral communication persist. Therefore, efforts to enhance policies and technological innovations in the referral system are required to improve services for cardiovascular emergency patients. Additionally, developing better communication networks and improving the competencies of medical personnel in handling emergency referrals are essential factors. The success of the referral system depends not only on technical preparedness but also on regulatory support and policies that facilitate rapid referral processes. The implementation of telemedicine systems, continuous training, and strengthening cross-sector healthcare coordination will significantly support the effectiveness of the referral system. With a holistic approach, the referral system can become more responsive in managing cardiovascular emergencies, ultimately reducing mortality rates and improving healthcare service quality.